Oxygen‐ and Sulfur‐bridged L‐shaped π‐Conjugated Molecules: Synthesis, Aggregated Structures, and Charge Transporting Behavior. Issue 11 (11th September 2018) - Okamoto, Toshihiro; Dosei, Hiroaki; Mitani, Masato; Murata, Yoshinori; Ishii, Hiroyuki; Nakamura, Ken‐ichi; Yamagishi, Masakazu; Yano, Masafumi; Takeya, Jun
Abstract: A series of oxygen‐ and sulfur‐bridged L‐shaped π‐electron cores (π‐cores) with Cs symmetry, dinaphtho [2,  1‐ b :2′, 3′‐ d ] furan (DNF−L ) and dinaphtho [2,  1‐ b :2′, 3′‐ d ] thiophene (DNT−L ), have been designed and investigated.DNF−L andDNT−L were successfully synthesized from commercially available 2‐methoxylnaphthalene in three and four steps, respectively. Notably, these compounds exhibited extremely high solubility in common organic solvents even without substituents and excellent thermal and chemical stability. X‐ray single‐crystal structural analyses ofDNF−L andDNT−L reveal that both molecules form herringbone‐type packing structures suitable for two‐dimensional charge transport, but the packing ofDNT−L has a large displacement in the direction of the longitudinal axis. Moreover, DNF−L shows a charge carrier mobility of up to 1.5 cm 2 /Vs in single‐crystal transistors, indicating that these L‐shaped molecules have excellent potential as organic semiconducting backbones with high solubility and high thermal and chemical stabilities. Abstract : Building bridges : A series of oxygen and sulfur‐bridged L‐shaped π‐cores, DNF−L andDNT−L, have been designed and investigated.DNF−L andDNT−L were successfully synthesized in three and four steps, respectively. Notably, these compounds exhibited extremely high solubility even without substituents and excellent thermal and chemical stability. Moreover, DNF−L shows a hole carrier mobility of up to 1.5 cm 2 /Vs in single‐crystal transistors, indicating thatDNF−L has potential as a scaffold for printable organic semiconducting π‐cores.